The Effect of Linear and Angular Midline Deviation on Smile Attractiveness Regarding Facial Height - behrad tanbakuchi; Sepideh Arab; Esfandiar Akhavan niaki; Mohamad moslem Imani; Sara Valizadeh; Ahmad Reza Shamshiri (Mashhad University of Medical Sciences, 2021)
Introduction: The aim of the present study was to evaluate ordinary people`s perception about smile attractiveness in long face and short face subjects with linear and angular midline deviations. Methods: Frontal facial smiling images of two young Iranian females (one short face and one long face) were manipulated by Adobe Photoshop CS3 software. Four photos with different linear midline deviations to right (1mm, 2mm, 3mm and 4mm) and four photos with counter clockwise angular midline deviation (2˚, 6˚, 10˚, 14˚) were produced. Sixty Iranian individuals (30 males and 30 females) were asked to determine from which photo on, they found that the smile is unattractive. Results: Unlike angular midline deviation, there was no statistically significant difference in the acceptability limitation for linear midline deviation between long face and short face subjects. The mean of unattractive limitation for angular midline deviation was 8.44˚ and 6.56˚ in long face and short face subjects, respectively. No statistically significant differences were found in ratings between male and female examiners. Conclusion: Angular midline deviation is more acceptable in long face people. On the other hand, the attractiveness of the two facial types is similarly affected by linear midline deviation